Government policy and housing rehabilitation in Wellington : a structural analysis : a thesis ... for the degree of Master of Arts in Geography at Massey University - Crawley, Clare Susan (Massey University, 1982)
Government intervention in the rehabilitation of housing stock in New Zealand, particularly through the introduction of the Community and Housing Improvement Programme, can be meaningfully analysed using a structuralist approach. Housing is marketed as a commodity in the capitalist system. It therefore reflects those relationships which are inherent in the operation of that system. Housing has special attributes as a commodity and has different use values for different interest groups. The ability of some groups to achieve the use values they wish to derive from housing is a reflection of their social, political and economic power and the relative investment and accumulation opportunities that use provides for capital, and not simply a matter of consumer preference. Housing rehabilitation policy is therefore able to provide assistance to certain groups involved with housing, but cannot provide solutions to all interest groups as the uses to which these groups wish to put housing are seldom harmonious. Government policy, as it has been put into practice in the three Wellington Neighbourhood Improvement Areas reinforces the existing inequalities in housing allocation. Government intervention in the housing market and the process of rehabilitation is an attempt to alleviate the most obvious hardships created by the operations of the capitalist system but it does not alter the basic structures from which these inequities arise. Housing policies designed to alleviate the problem of deterioration of older housing stock cannot provide solutions to other housing problems, including those faced by the lower socio-economic groups. As long as housing is treated as a commodity it will provide opportunities for capital gain to diverse interest groups.
Keywords: Housing rehabilitation -- Wellington; Housing policy; New Zealand